2022
DOI: 10.1111/bjd.21619
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory skin diseases and wounds

Abstract: Inflammatory wounds of the skin can be caused by many different diseases. Of particular importance here are the very heterogeneous groups of vasculitides and vasculopathies. These are usually interdisciplinary relevant diseases that require extensive diagnostics in specialized centres. Clinically, these inflammatory wounds present as very painful ulcers that develop from necrosis and are surrounded by erythematous livid borders. The healing process is often difficult and protracted. Moreover, it considerably i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 78 publications
0
12
0
1
Order By: Relevance
“…83 , 84 Likewise, in patients with immune dysfunction, diabetes or circulatory pathologies, bacteria may overwhelm the immune system and any antimicrobial treatments, which makes infected chronic wounds in these patients also highly difficult to treat. 85 Treatments of difficult‐to‐heal wounds including in patients with comorbidities are established in daily clinical practice, 86 but the majority of therapeutic interventions, particularly with regards to the usage of wound dressings, lacks robust and rigorous data concerning efficacy, which is vital for determining for whom and when specifically, each treatment and product type should be used. 87 , 88 The healthcare costs associated with this sub‐optimal treatment of wounds, in the absence of this critical information, is vast.…”
Section: Discussionmentioning
confidence: 99%
“…83 , 84 Likewise, in patients with immune dysfunction, diabetes or circulatory pathologies, bacteria may overwhelm the immune system and any antimicrobial treatments, which makes infected chronic wounds in these patients also highly difficult to treat. 85 Treatments of difficult‐to‐heal wounds including in patients with comorbidities are established in daily clinical practice, 86 but the majority of therapeutic interventions, particularly with regards to the usage of wound dressings, lacks robust and rigorous data concerning efficacy, which is vital for determining for whom and when specifically, each treatment and product type should be used. 87 , 88 The healthcare costs associated with this sub‐optimal treatment of wounds, in the absence of this critical information, is vast.…”
Section: Discussionmentioning
confidence: 99%
“…Skin wounds are caused by various intrinsic pathological and external mechanical factors that damage the structure or integrity of skin tissues [ 1 ]. Skin wounds can lead to a series of local and even systemic physiological and pathological changes, which result in a heavy burden on patients and society.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in inflammation can result in chronic wounds and include a range of inflammatory skin diseases. It has been shown that 3–5% of skin ulcers are due to vasculitis, and vasculopathy resulting in calciphylaxis is present in 5% of patients with end‐stage renal disease 3 . The treatment options for inflammatory ulcers include the use of topical and systemic steroids and immunosuppressive drugs.…”
mentioning
confidence: 99%
“…In the Scholarly Review on chronic wounds in this edition of the BJD we have produced comprehensive and concise reviews of four aspects of this orphan subject. [1][2][3][4] It is anticipated that after reading these papers there would be greater acceptance that this clinical problem requires urgent, systematic and comprehensive investment and support that results in patients receiving quality care from a range of clinical staff and specialities as today wounds are seen by many as a subject with no legitimate home or clinical focus.…”
mentioning
confidence: 99%
See 1 more Smart Citation